Integrative Transcriptome and Metabolome Profiles Reveal Common and Unique Pathways Involved in Seed Initial Imbibition Under Artificial and Natural Salt Stresses During Germination of Halophyte Quinoa - Yan, Huifang; Nie, Yuting; Cui, Kailun; Sun, Juan (Frontiers in Plant Science, 2022)
Salt stress is a major environmental factor that seriously restricts quinoa seed germination. However, the key regulatory mechanisms underlying the effect of salt stress on the initial imbibition stage of quinoa seeds are unclear. In this study, dry seeds (0 h) and imbibed (8 h) seeds with 450 mM NaCl (artificial salt) and 100% brackish water of Yellow River Estuary (BW, natural salt) were used to assess the key salt responses based on germination, transcriptome, and metabolome analyses. The results indicated that the capacity of germinating seeds to withstand these two salt stresses was similar due to the similarities in the germination percentage, germination index, mean germination time, and germination phenotypes. Combined omics analyses revealed that the common and unique pathways were induced by NaCl and BW. Starch and sucrose metabolism were the only commonly enriched pathways in which the genes were significantly changed. Additionally, amino sugar and nucleotide sugar metabolism, and ascorbate and aldarate metabolism were preferably enriched in the NaCl group. However, glutathione metabolism tended to enrich in the BW group where glutathione peroxidase, peroxiredoxin 6, and glutathione S-transferase were significantly regulated. These findings suggest that the candidates involved in carbohydrate metabolism and antioxidant defense can regulate the salt responses of seed initial imbibition, which provide valuable insights into the molecular mechanisms underlying the effect of artificial and natural salt stresses.